Access to Finance and Job Growth: Firm-Level Evidence across Developing Countries - Ayyagari, Meghana; Juarros, Pedro; Martinez Peria, Maria Soledad; Singh, Sandeep (Review of Finance, 2021)
Abstract This paper investigates the effect of access to finance on job growth in over 780,000 firms across twenty-two developing countries. Using the introduction of credit bureaus as an exogenous shock to the supply of credit, the paper finds that increased access to finance results in higher employment growth, especially among micro, small, and medium enterprises. The results are robust to using firm-fixed effects, industry measures of external finance dependence, and propensity score matching. Our findings have implications for policy interventions targeted to produce job growth.